Legislation shortage as an obstacle for social work practice - Maximova Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article discovers problem of social services activity legislation support improving. It is shown that current legislation system shortcoming slow down the social worker task realisation. The article shows examples of lack of legislation negative influence on problems of adolescence criminality prevention and activity with families involved in complex life situation. The directions of abovementioned problems solving are presented.